The Process and Significance of Political Scandals: A Comparison of Watergate and the "Sewergate" Episode at the Environmental Protection Agency. (4th August 2014) - Szasz, Andrew
Abstract : Purposeful scandalmongering is a familiar and particularly dramatic feature of the American political process. If successful, it embarrasses one's political opponents, blocks their policies, and perhaps even drives them from office. This paper compares Watergate, the most important recent example of political scandal, and "Sewergate, " the 1983 episode at the U.S. Environmental Protection Agency. Based on this comparison, I develop a conceptual framework that describes the course or trajectory of scandal. I then evaluate what effects the two episodes had on substantive policy and on mass political attitudes. I find that neither Watergate nor Sewergate had much enduring impact and conclude by discussing the significance of scandals in light of their rather modest long-term consequences.